Helicosporium luteosporum sp. nov. and Acanthohelicospora aurea (Tubeufiaceae, Tubeufiales) from terrestrial habitats - Lu, Yong-Zhong; Boonmee, Saranyaphat; Bhat, D. Jayarama; Hyde, Kevin D.; Kang, Ji-Chuan (Phytotaxa, 2017)
Morphological characters and molecular data are currently used to identify and confirm genotypic and phenotypic distinctions and connections in fungi. In this paper, we introduce Helicosporium luteosporum sp. nov. based on morpho-phylogenetic traits. The species is characterized by shiny yellow colonies on woody substrates, erect pigmented conidiophores with denticulate conidiogenous cells and coiled conidia. Phylogenetic analysis of combined ITS, LSU and TEF1α sequence data place H. luteosporum as a distinct lineage among other Helicosporium species. In addition, both sexual and asexual morphs of Acanthohelicospora aurea were found from different specimens and their relationship is confirmed by molecular data.